Jinhua Qinggan granules for non-hospitalized COVID-19 patients: A double-blind, placebo-controlled, and randomized controlled trial - Shah, Muhammad Raza; Fatima, Samreen; Khan, Sehrosh Naz; Ullah, Shafi; Himani, Gulshan; Wan, Kelvin; Lin, Timothy; Lau, Johnson Y. N.; Liu, Qingquan; Lam, Dennis S. C. (Frontiers in Medicine, 2022)
Key findings from the World Health Organization Expert Meeting on Evaluation of Traditional Chinese Medicine in treating COVID-19 reported that TCMs are beneficial, particularly for mild-to-moderate cases. The efficacy of Jinhua Qinggan Granules (JHQG) in COVID-19 patients with mild symptoms has yet to be clearly defined. Methods: We conducted a phase 2/3, double-blind, randomized, placebo-controlled trial to evaluate the efficacy and safety of treatment with JHQG in mild, nonhospitalized, laboratory-confirmed COVID-19 patients. Participants were randomly assigned to receive 5g/sacket of JHQG or placebo granules orally thrice daily for 10 days. The primary outcomes were the improvement in clinical symptoms and proportion tested negative on viral PCR after treatment. Secondary outcomes were the time to recovery from clinical symptoms and changes in white blood cells (WBC) and acute phase reactants (C-reactive protein (CRP) and ferritin) on 10th day after treatment initiation. Results: A total of 300 patients were randomly assigned to receive JHQG (150 patients) and placebo (150 patients). Baseline characteristics were similar in the two groups. In the modified intention-to-treat analysis, JHQG showed greater clinical efficacy (82.67%) at 10th day of the trial compared with the placebo group (10.74%) (rate difference: 71.93%; 95% CI 64.09 - 79.76). The proportion of patients with a negative PCR after treatment were comparable (rate difference: -4.67%; 95% CI -15.76 - 6.42). While all changes in WBC, ferritin, and CRP levels showed a statistically significant decline in JHQG (P≤0.044) after treatment, but not the latter in placebo (P=0.077). The median time to recovery of COVID-19 related symptoms including cough, sputum, sore throat, dyspnea, headache, nasal obstruction, fatigue, and myalgia were shorter in the JHQG group compared to the placebo group (P<0.001 for all). 3 patients experienced mild to moderate adverse events during the treatment period in the JHQG group. Findings were similar between the modified intention-to-treat and the per-protocol analysis that included only patients who reported 100% adherence to the assigned regimen. Conclusions: Based on the time to recover from the COVID-19 related symptoms and adverse events, it is concluded that JHQG is a safe and effective TCM for symptomatic relief of mild COVID-19 patients